Differing Identities but Comparably High HIV and Bacterial Sexually Transmitted Disease Burdens Among Married and Unmarried Men Who Have Sex With Men in Mumbai, India. Issue 11 (November 2015) - Mayer, Kenneth H.; Gangakhedkar, Raman; Sivasubramanian, Murugesan; Biello, Katie B.; Abuelezam, Nadia; Mane, Sandeep; Risbud, Arun; Anand, Vivek; Safren, Steven; Mimiaga, Matthew J.
Abstract : Background: Although HIV incidence has declined in India, men and transgender women who have sex with men (MSM) continue to have high rates of HIV and sexually transmitted disease (STD). Indian MSM face substantial pressures to marry and have families, but the HIV/STD burden among married Indian MSM is not well characterized. Methods: A diverse sample of Indian MSM were recruited through respondent-driven sampling. Independent variables that produced a P value of 0.10 or less were then added to a multivariable logistic regression model. Results: Most of the 307 MSM (95 married and 212 unmarried) recruited into the study were younger than 30 years, and less than one-third had more than a high school education. Almost two-thirds of the married men had children, compared with 1.4% of the unmarried men ( P < 0.001). The numbers of condomless anal sex acts did not differ by marriage status. Although unmarried MSM more often identified themselves as "kothi" (receptive role), their rates of HIV or bacterial STD were similar to married MSM, with 14.3% being HIV infected. The respondent-driven sampling–adjusted prevalence of any bacterial STD was 18.3% for married MSM and 20% for unmarried MSM (not significant). Participants reported high levels of psychological distress, with 27.4% of married and 20.1% of unmarried MSM reporting depressive symptoms (not significant). Conclusions: Men who have sex with men in Mumbai had high rates of HIV, STD, and behavioral health concerns. Clinicians need to become more comfortable in eliciting sexual histories so that they can identify MSM who need HIV/STD treatment and/or prevention services. Abstract : A respondent-driven sample of men who have sex with men in Mumbai found high HIV and sexually transmitted disease rates, which did not differ by marital status. Respondents reported high levels of psychological distress.